Rapid recruitment of CD14+ monocytes in experimentally induced allergic rhinitis in human subjects - Eguiluz-Gracia, Ibon; Dollner, Ralph (The journal of allergy and clinical immunology, 2016)
Background - Activated TH2 cells and eosinophils are hallmarks of the allergic inflammation seen in patients with allergic rhinitis (AR). However, which cells activate and attract T cells and eosinophils to the inflammatory lesion has not been determined. - Objective - We wanted to assess the role of mucosal mononuclear phagocytes, consisting of monocytes, macrophages, and dendritic cells, in the local allergic inflammatory reaction. - Methods - Patients with AR and nonatopic control subjects were challenged with pollen extract, and nasal symptoms were recorded. Mucosal biopsy specimens obtained at different time points before and after challenge were used for immunostaining in situ and flow cytometric cell sorting. Sorted mononuclear phagocytes were subjected to RNA extraction and gene expression profiling. - Results - In an in vivo model of AR, we found that CD14+ monocytes were recruited to the nasal mucosa within hours after local allergen challenge, whereas conventional dendritic cells accumulated after several days of continued provocation. Transcriptomic profiling of mucosal mononuclear phagocytes sorted after 1 week of continued allergen challenge showed an activated phenotype at least partially driven by IL-4 signaling, IL-13 signaling, or both. Importantly, gene expression of several TH2-related chemokines was significantly upregulated by the mononuclear phagocyte population concomitant with an increased recruitment of CD4+ T cells and eosinophils. - Conclusion - Our findings suggest that the mononuclear phagocyte population is directly involved in the production of proinflammatory chemokines that attract other immune cells. Rapid recruitment of CD14+ monocytes to the challenged site indicates that these proinflammatory mononuclear phagocytes have a central role in orchestrating local allergic inflammation.
Gesehen am 17.06.2019
Im Titel ist "+" hochgestellt
Seitenangaben nach Vorlage: 1872-1881.e12